Immigration and Integration in the European Union - Repez, Filofteia; Olar, Polixenia (Acta Universitatis Danubius. Relationes Internationales, 2024)
Immigration has become a fact of life in the European Union, a social phenomenon. Therefore, integration policies for immigrants have an important role. It is recognized that immigration and the integration of immigrants have become, and will probably remain, a sensitive issue from a political and societal point of view. Many European Union documents state that successful integration contributes to addressing some of the challenges currently faced by member states, such as the high cost (human and social) of economic exclusion, distrust in the fairness of public systems or the spread of all forms of ideologies extremist. Integration and immigration are debated topics in academia both for theoretical clarifications and for practical contributions by identifying appropriate solutions to the negative aspects of the integration process. Based on these considerations, the article aims, as objectives, to present: some definitions of integration, the approach of Professor Yuval Noah Harari regarding immigration within the European Union, some statistics on immigration in the European Union and aspects of the European Union's immigration policy.